The association of music preferences and depressive symptoms in high school students: A community-based study from Istanbul - SABUNCUOĞLU, OSMAN TALAT (SAGE PUBLICATIONS INC, 2013)
We investigated the association of music preferences with depressive symptoms among high school students in Istanbul; 10th-, 11th- and 12th-grade students (N = 1226) were chosen for the study. The Children's Depression Inventory (CDI) and a detailed, semi-structured, self-report inquiry assessing music preferences and various psychosocial variables were administered to the students. Adolescents reporting heavy metal music and arabesque music in their playlists had significantly higher CDI total scores compared to adolescents who did not report these genres in their playlists. The percentage of students with problematic parent relations was highest for those with preferences for heavy metal music. Alcohol use was highest among students with preferences for dance/hip-hop music, followed by those with preferences for heavy metal. Negative thoughts and feelings when listening to music were related to higher CDI scores regardless of the favourite music genre. Future studies are needed to clarify the relationship between music preferences and specific psychopathologies in adolescents.
Keywords: adolescent; depression; heavy metal; music preference; rap; HEAVY-METAL MUSIC; RAP MUSIC; ADOLESCENTS; LYRICS; PERSONALITY; BEHAVIORS; TRENDS; MEDIA; YOUTH; STYLE